Comparative Relationships Between Personality Traits and Self-Efficacy on Social Adjustment among Secondary School Students in Delta State, Nigeria (Federal University Gusau Faculty of Education Journal, 2025)
This study examined the relationship between personality traits (extraversion, neuroticism, conscientiousness) and social adjustment among secondary school students in Delta Central Senatorial District of Delta State. The study was necessitated by the increasing concern among parents, teachers, counsellors, and psychologists about how students adapt socially in school environments. The population comprised all Senior Secondary School One (SS1) and Senior Secondary School Two (SS2) students in the Senatorial District, and data were collected using three instruments: the Personality Traits Assessment Questionnaire (PTAQ), the General Self-Efficacy Scale (GSES), and the Social Adjustment Questionnaire (SAQ). The findings revealed that extraversion personality trait had a significant positive relationship with students’ social adjustment, showing that students who were more outgoing and sociable adjusted better socially. Similarly, self-efficacy demonstrated a strong positive relationship with social adjustment, particularly through mastery experiences and vicarious experiences, which were found to be more influential than verbal persuasion. Finally, the combined analysis showed that personality traits and self-efficacy jointly had a strong and significant relationship with students’ social adjustment, accounting for over 70% of the variation in adjustment levels. Based on these findings, the study concluded that both personality traits and self-efficacy are critical factors in shaping how students relate with peers and adapt to school life. It was recommended that schools should implement structured social engagement programs, such as leadership training, debate clubs, and peer mentorship, to strengthen students’ social adjustment. Counsellors and teachers should also design interventions that build students’ self-efficacy through mastery and vicarious experiences. Furthermore, educational policymakers should integrate personality development and self-efficacy enhancement strategies into school curricula to promote holistic student adjustment.